Ta có: tan(n+1)x−tannx=sin(n+1)xcos(n+1)x−sinnxcosnx=sin(n+1)x.cosnx−sinnx.cos(n+1)xcos(n+1)x.cosnx=sin[(n+1)x−nx]cos(n+1)x.cosnx=sinxcos(n+1)x.cosnxSuy ra: $\frac{1}{{\cos (n + 1)x.\cos nx}} = \frac{1}{{\sin x}}{\rm{[}}\tan (n + 1)x - \tan nx{\rm{]}}Từđó:A = \frac{1}{{\sin x}}{\rm{[}}\tan 2x - \tan x{\rm{] + }}\frac{1}{{\sin x}}{\rm{[}}\tan 3x - \tan 2x{\rm{] + }}...{\rm{ + }}\frac{1}{{\sin x}}{\rm{[}}\tan 2013x - \tan 2012x{\rm{]}}= \frac{1}{{\sin x}}{\rm{[}}\tan 2013x - \tan x{\rm{]}}Mà\tan \frac{{2013\pi }}{{2012}} = \tan (\pi + \frac{\pi }{{2012}}) = \tan \frac{\pi }{{2012}}Thếx = \frac{\pi }{{2012}}vàoAtađược:A = \frac{1}{{\sin \frac{\pi }{{2012}}}}[\tan \frac{{2013\pi }}{{2012}} - \tan \frac{\pi }{{2012}}] = 0$
Ta có:
tan(n+1)x−tannx=sin(n+1)xcos(n+1)x−sinnxcosnx=sin(n+1)x.cosnx−sinnx.cos(n+1)xcos(n+1)x.cosnx=sin[(n+1)x−nx]cos(n+1)x.cosnx=sinxcos(n+1)x.cosnxSuy ra: $\frac{1}{{\cos nx.\cos
(n
+ 1)x}} = \frac{1}{{\sin x}}[\tan (n + 1)x - \tan nx]
Từđó:A = \frac{1}{{\sin x}}{\rm{[}}\tan 2x - \tan x{\rm{] + }}\frac{1}{{\sin x}}{\rm{[}}\tan 3x - \tan 2x{\rm{] + }}...{\rm{ + }}\frac{1}{{\sin x}}{\rm{[}}\tan 2013x - \tan 2012x{\rm{]}}
= \frac{1}{{\sin x}}{\rm{[}}\tan 2013x - \tan x{\rm{]}}
Mà\tan \frac{{2013\pi }}{{2012}} = \tan (\pi + \frac{\pi }{{2012}}) = \tan \frac{\pi }{{2012}}
Thếx = \frac{\pi }{{2012}}
vàoAtađược:A = \frac{1}{{\sin \frac{\pi }{{2012}}}}[\tan \frac{{2013\pi }}{{2012}} - \tan \frac{\pi }{{2012}}] = 0$